UNGKAPAN LARANGAN PADA MASYARAKAT NAGARI LANSEK KADOK KECAMATAN RAO SELATAN KABUPATEN PASAMAN - Ramadhani, Nadia; krisna, Eva; Muhardis, Muhardis (Pendidikan Bahasa Indonesia, 2013)
The phrase speech ban is believed to contain a ban if not complied with will be rewarded . Ban expression can be used to educate members of the public to know the manners of behaving . If only given a warning by regular expressions , they did not heed it . Ban any expression that is accompanied by rewards , then they will stick with it . Social functions contained in the prohibition of expression should be preserved because it is enrich with Minangkabau .This study aims to describe the expression of a ban on the social function Lansek Kadok Nagari , District of South Rao , Pasaman . Type of this research is descriptive qualitative research method . The theory used in this research is partly verbal folklore . Data collection is done by : ( 1 ) the situation of the environment and conditions of speakers , (2 ) conduct interviews and record phrases delivered ban speakers using an audio recorder , and ( 3 ) record the biodata speakers .Based on the research findings and discussion summarized as follows . Found 44 ban on public expression Lansek Kadok South Rao Pasaman . In the words of as many as 5 tesebut ban ban expression that has the social function of religion or belief emotion thickening , 21 idiom ban that has the social function of education of children and adolescents , and as many as 18 expressions ban which has a social function explanation acceptable reason some folk .